The happiness of Young Australians: Empirical Evidence on the Role of Labour Market Experience - Dockery, Alfred Michael (Blackwell Publishing Asia, 2005)
Data from the Longitudinal Surveys of Australian Youth are used to investigate factors that influence young Australians' self-reported levels of 'happiness' during the school-to-work transition, focusing on the role of labour market experience. Panel logit models are fitted to control for individual effects. Fixed individual personality traits and marital status strongly influence reported happiness. There is evidence of declining well being with duration of unemployment and of the importance of job quality, rather than just having a job. The validity of Clark and Oswald's (1994)assertion that empirical findings from happiness research show that unemploymentis involuntary is questioned.